Deconstructing orthographic knowledge and cultural awareness of miswak practice amongst dental educators: benefits and barriers: a qualitative study - Che Musa, Muhd Firdaus; Muhammad Ali, Suhaila; Mohd, Farah Natashah; Ab Halim, Noorhazayti (Wolters Kluwer ‑ Medknow, 2020)
Aim: Miswak is a chewing stick used for oral hygiene and has both cultural and religious heritage. Concerns have emerged about the limitation of evidences on its effectiveness and guidance to practice. This study aims to explore dental educators’ perceived level of knowledge and awareness of Miswak practice and teaching as oral hygiene tool. Materials and Methods: Dental educators with various socio-religious demographic backgrounds at International Islamic University of Malaysia(IIUM) University were invited to participate in an audio-taped focus group discussion in 2017, conducted in English using a pre-tested topic guide. The qualitative data were recorded, transcribed, and analysed using a Framework Analysis. Results: The dental educators (n = 11) from various socio-religious and educational backgrounds demonstrated low-medium level of knowledge on Miswak given there are limited, restricted, and localized evidences, influenced by their culture, religious values, and past educational training and several domains of practice. This has an implication on their low level of awareness to practice Miswak considering the fact that the barrier identified is more than its benefit. Furthermore, there was a strong mixed sense of valuing evidence-based knowledge and cultural–religious belief among dental educators of postmodern society in meeting both oral health needs and social expectations. Conclusions: Educators of postmodern society with western educational background view metaphorically the level of knowledge and awareness of Miswak usage, although most of them are Asian and Muslim. A flexible strategy is needed to overcome the poor dissemination of Miswak evidence to further educate dental educators in order to frame a Miswak educational guideline for the benefit of society.